CHILDHOOD PRIMARY TUBERCULOSIS IN RAMATHIBODI HOSPITAL, RADIOGRAPHIC MANIFESTATIONS - THANAMEE, Siriporn; BALACHANDRA, Shashilekha (The ASEAN Journal of Radiology, 2023)
The aim of this study was to review the radiologic features of primary tuberculosis in childhood and to determine whether there is any significant difference in the pattern of disease which occurs among different age groups. Chest radiographs of 84 children with pediatric primary tuberculosis who were treated at Ramathibodi hospital were reviewed. Pulmonary infiltration was found in 84.09% of the cases and was the most common abnormality identified on the initial chest radiograph. The infiltration was more common in the right lung. Lymphadenopathy was found in 72.73% that typically involved the hilar and paratracheal regions. Both the younger (0-5 years old) and the older (6-15 years old) children had high prevalence of parenchymal abnormalities and lymphadenopathy.